Results of the attitude reconstruction for the UniSat-6 microsatellite using in-orbit data - Battistini, Simone; Cappelletti, Chantal; Graziani, Filippo (Elsevier, 2016)
UniSat-6 is a civilian microsatellite that was launched in orbit on the 19th of June, 2014. Its main mission consisted in the in-orbit release of a number of on-board carried Cubesats and in the transmission to the UniSat-6 ground station of telemetry data and images from an on-board mounted camera. The spacecraft is equipped with a passive magnetic attitude control system. Gyros and magnetometers provide the information about the attitude of the spacecraft.